Maximizing sponsorship deals for sports clubs & organizations through strategic marketing frameworks - Ševčík, Michal; Machek, Martin; Bartošek, Daniel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This master's thesis aims to develop a strategic marketing framework for sports organizations to maximize sponsorship deals. It investigates how sponsorship practices are shaped and influence the strategic value of these relationships. The research employed a qualitative methodology, conducting semi-structured in-depth interviews with nineteen experts from sports entities and sponsoring companies. Data was analyzed using thematic coding. Key results highlight the critical importance of strategic alignment, individualized proposals, long-term partnerships, proactive outreach, diverse asset articulation, including digital & emotional value, and robust activation. The study concludes that effective sponsorship requires a holistic, relational approach, and it introduces the "Strategic Sponsorship Excellence Framework" to guide organizations.
Vedoucí práce: Martin Machek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses